Factors influencing IFRS 13 adoption in enhancing financial report accuracy - Mehrani, Sasan; Tofiq, Adalet (Edelweiss Applied Science and Technology, 2025)
This study aims to identify the factors affecting the adoption of IFRS 13 and its significance in improving financial report accuracy among employees at various financial institutions in Erbil, Iraq. The research unveils various findings that require further exploration, such as the roles of regulatory factors, organizational dynamics, market pressures, technical expertise and knowledge, economic conditions, and external influences on educational or professional development incorporated with institutionalism in IFRS 13 adoption. This finding of the current study illustrates clearly that the adoption of IFRS 13 does significantly improve accuracy, clarity, and reliability in financial reporting thereby giving a clearer picture to stakeholders for making informed decisions. Second, the research highlights that educational and professional development, organizational practices, or technical expertise are fundamental for enhancing IFRS 13 adoption success as well as financial reports accuracy that can be driven by IFRS 13. The findings have some practical implications for financial institutions, regulators, and policymakers. Continuous education and training programs and internal controls should be strengthened and increased support from the regulatory bodies may help in faster membership achievement of IFRS 13 compliance requirements. This research could be extended to study the long-term implications of IFRS 13 adoption, how technology can support and promote this implementation process, and cultural factors in different industries and across geographical areas that may affect an agent’s willingness to use such measurements.